Curcumin Hybrid Lipid Polymeric Nanoparticles: Antioxidant Activity, Immune Cellular Response, and Cytotoxicity Evaluation - Quirós Fallas, María isabel (2022)
Poor solubility and short biological half-life present a challenge that needs to be overcome in order to improve the recognized bioactivities of curcumin (CUR), the main phenolic compounds derived from the roots of Curcuma longa. However, drug delivery systems have proven to be an excellent strategy to improve and obtain greater bioavailability. Our previous studies on curcuminoid hybrid nanoparticles have shown promising results by significantly increasing the solubility of desmethoxycurcumin (DMC) and bisdemethoxycurcumin (BDM). In this contribution, we performed a detailed characterization of a CUR as well as in vitro and in vivo studies. The developed method produced CUR loaded nanoparticles with an average size of 49.46 ± 0.80. Moreover, the FT-IR analysis confirmed the encapsulation, and TEM images showed their spherical shape. The NP achieved an encapsulation efficiency greater than 99%. Further, the release studies found that the NPs obtained a significantly higher release than the pure compounds in water. In vivo delayed-type hypersensitivity (DTH) studies showed promising results by enhancing the immune activity response of CUR in NP compared to bulk CUR. Furthermore, we report a significant increase in antioxidant activity for CUR-NP in aqueous solution compared to free CUR. Finally, an important in vitro cytotoxic effect on gastric AGS and colon SW620 adenocarcinoma cell lines was found for CUR-NP while empty carrier nanoparticles are observed to exhibit low cytotoxicity, indicating the potential of these CUR-PLU NPs for further studies to assess their phytotherapeutic applications.